Klasifikasi Ilustrasi Decoupage Tas Rotan Khas Bali Sebagai Informasi Perkembangan Desain Industri - Jessica Yonatia (JURNAL RUPA, 2020)
Bali is one of tourism destination that have various and fascinating tourist objects, such as nature, culinary, culture and Bali’s signature handicrafts. Rattan bags made with Ate wood as main material is one of Bali’s signature handicraft that is currently popular because of it’s interesting shape and the using of unique material. The popularity of Balinese rattan bags increases since both local and foreign fashion bloggers often post the bags as ootd (outfit of the day) in their social media. Some Balinese masons did some innovation to elevate the visual aesthetic of the bags through adding decoupage technique illustrations. Data collection method that applied is structured interviews with Bali local craftmen, observation and study literature, in a year and a half period. Qualitative research method applied to reach the goal of the research, which is to review the development of illustration designs on Balinese rattan bags during late of 2017 until middle of 2019, by the choosing of visual object (flora and fauna) that most shown, colour majority and visual design composition, and the relation of those visual elements with Balinese traditional elements.